Phenotypic and genotypic characterization of vancomycin-resistant enterococci in a university hospital of southern Italy (Italian Journal of Public Health, 2007)
Background: In the last decades vancomycin-resistant enterococci (VRE) have emerged as important pathogens responsible for hospital-acquired infections. To analyze the spread and clonal relatedness of VRE, a two-year study of isolates was carried out in the hospital of the University “Federico II” in Naples.Methods: Enterococcus species were identified by using API-2 Strep and antibiotic susceptibility was determined through the use of four tests: disk diffusion, broth dilution methods, Etest and Vitek 2. Polymerase Chain Reaction (PCR) was used to analyse glycopeptide resistance. Pulsed-field gel electrophoresis (PFGE) and arbitrarily primed (AP)-polymerase chain reaction were used for molecular typing of the strains.Results: Thirty-two isolates of enterococci (18 E. faecium and 14 E. faecalis) showed resistance to vancomycin and teicoplanin and all the strains were vanA-positive. AP-PCR showed a unique clone of E. faecium, as well as for E. faecalis isolates. Identical results were obtained by PFGE for E. faecalis isolates, while three different PFGE patterns emerged for E. faecium.Conclusions: The low degree of genetic diversity among the isolates strongly suggests a clonal spread of antibiotic-resistant strains among hospitalized patients in high-risk wards. This report represents the first step to understanding VRE spread in our hospital as well as contributing to the comparison among different antibiotic susceptibility tests and molecular typing methods.
Keywords: Vancomycin-resistant enterococci; antibiotic susceptibility; genotyping; PFGE; AP-PCR